Study on the Atomization and Dust-Reduction Performance of a New Type of External Pneumatic Vortex Fog Curtain Dust Removal Device in Fully Mechanized Excavation Face - Deji Jing; Rina An; Jingxu Chen; Shaocheng Ge; Liying Sun (Advances in Materials Science and Engineering)
To solve the problem of dust pollution in the heading face, a new type of external pneumatic vortex fog curtain dust removal device suitable for a fully mechanized excavation face is designed in this paper. Firstly, dust migration laws at different times are simulated and analyzed by COMSOL software, and the functional relationship of dust concentration distribution above 50 mg/m3 at different heights and different wind speed is derived. Aiming at the dust migration laws of the heading face, a new dust removal device was proposed, and the atomization performance of the new type of external pneumatic vortex fog curtain dust removal device under different jet wind speed, different atomization pressure, and different nozzle working angle is explored through atomization performance experiment. It is found that when jet wind speed is 30 m/s, atomization pressure is 4 MPa, and nozzle working angle is 75°, the atomization performance of the new type of external pneumatic vortex fog curtain dust removal device is the best. Through the simulation of COMSOL software, the influence of air volume on the new type of external pneumatic vortex fog curtain dust removal device is analyzed. It is found that the new type of external pneumatic vortex fog curtain dust removal device is relatively stable when the air volume at the pressure outlet is less than 400 m3/min. The dust-reduction efficiency of the new type of external pneumatic vortex fog curtain dust removal device was investigated through the dust-reduction experiment, and it is found that the new type of external pneumatic vortex fog curtain dust removal device had better dust removal performance under the condition that the ventilation conditions did not interfere with the integrity of the vortex fog curtain.